Nanopore Formation at the Junctions of the Polycrystal Intergranular Boundary Under Plastic Deformation - Suchikova, Y.; Kovachov, S.; Lazarenko, A.; Bohdanov, I.; Popov, Anatoli I. (Sciendo, 2023)
The article is devoted to the study of the mechanism of nanopore formation in the junctions of polycrystal grains under the plastic deformation of a polycrystal due to the conservative sliding of lattice dislocations. A mechanism for the formation of a stress concentrator at the junction of the polycrystal grain boundaries is proposed. The possibility of relaxation of the stress state due to the formation of a junction nanopore is considered in the paper. --//-- This is an open-access article Suchikova, Y., Kovachov, S., Lazarenko, A., Bohdanov, I. and Popov, A. I.. "Nanopore Formation at the Junctions of the Polycrystal Intergranular Boundary Under Plastic Deformation" Latvian Journal of Physics and Technical Sciences, vol.60, no.6, 2023, pp.3-18. https://doi.org/10.2478/lpts-2023-0033 published under the CC BY-NC-ND 4.0 licence.
The study has been supported by the Ministry of Education and Science of Ukraine via Project No. 0122U000129 “The search for optimal conditions for nanostructure synthesis on the surface of A3B5, A2B6 semiconductors and silicon for photonics and solar energy”, Project No. 0121U10942 “Theoretical and methodological bases of system fundamentalization of the future nanomaterials experts training for productive professional activity”, and Project No. 123U100110 “System of remote and mixed specialized training of future nanoengineers for the development of new dual-purposaterials”. In addition, the research of A.I.P. and Y.S. has been partly supported by COST Action CA20129 “Multiscale irradiation and chemistry driven processes and related technologies” (MultiChem). A.I.P. thanks the Institute of Solid-State Physics, University of Latvia, ISSP UL as the Centre of excellence, supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Dislocation; grain boundaries; junction; nanopores; polycrystal; stress concentrators